2023
DOI: 10.1038/s41598-023-28729-3
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety and post-traumatic stress during the 2022 Russo-Ukrainian war, a comparison between populations in Poland, Ukraine, and Taiwan

Abstract: Ukraine has been embroiled in an increasing war since February 2022. In addition to Ukrainians, the Russo-Ukraine war has affected Poles due to the refugee crisis and the Taiwanese, who are facing a potential crisis with China. We examined the mental health status and associated factors in Ukraine, Poland, and Taiwan. The data will be used for future reference as the war is still ongoing. From March 8 to April 26, 2022, we conducted an online survey using snowball sampling techniques in Ukraine, Poland, and Ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 31 publications
2
57
0
4
Order By: Relevance
“…Less affluent persons were more affected by fears regarding their personal financial situation related to the war than more affluent persons. The findings are relevant on a global level, as studies conducted immediately after the start of the war demonstrate a significant impact on mental health in countries beyond Ukraine and its neighboring countries ( 5 , 15 ). Our study contributes to this body of knowledge by showing that the effects persist for up to 6 months after the initial shock of the war and may result in persistent mental health sequelae, particularly for already vulnerable groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Less affluent persons were more affected by fears regarding their personal financial situation related to the war than more affluent persons. The findings are relevant on a global level, as studies conducted immediately after the start of the war demonstrate a significant impact on mental health in countries beyond Ukraine and its neighboring countries ( 5 , 15 ). Our study contributes to this body of knowledge by showing that the effects persist for up to 6 months after the initial shock of the war and may result in persistent mental health sequelae, particularly for already vulnerable groups.…”
Section: Discussionmentioning
confidence: 89%
“…A war has been shown to lead to higher prevalence of anxiety, mood disorders and posttraumatic stress disorder (PTSD) in the general population of the affected country during and for years post-war ( 2 , 3 ). The ongoing war in Ukraine has already been shown to have detrimental impacts on the mental health of Ukrainian military and civilian combatants ( 4 ) and the Ukrainian general population ( 5 ) with nearly half of the participants in both studies displaying clinically relevant symptoms of depression and anxiety. Persons who are internally displaced due to the ongoing conflict between Russia and Ukraine are at an especially high risk for mental health sequelae ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…show that sources of decreased GDP include trade and financial market frictions, respectively. Further, the disappearance of entrepreneurial activity might be one factor behind the identified mental health consequences of the Russo-Ukrainian war (Bai et al, 2022;Chudzicka-Czupała et al, 2023;Jawaid et al, 2022;Kossowska et al, 2023).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In an online cross‐sectional study of the psychological effects of the Russian‐Ukrainian war, Chudzicka‐Czupała et al (2023) examined the mental health status of participants from Ukraine, Poland and Taiwan. Findings showed that Ukrainian participants reported significantly higher scores in depression, anxiety, stress and post‐traumatic stress.…”
Section: Media Exposure To Violence and Psychological Reactionsmentioning
confidence: 99%